2023
DOI: 10.3390/biomimetics8010042
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Diversity Underpins Future Biomimetic Replications

Abstract: Although the evolution of tooth structure seems highly conserved, remarkable diversity exists among species due to different living environments and survival requirements. Along with the conservation, this diversity of evolution allows for the optimized structures and functions of teeth under various service conditions, providing valuable resources for the rational design of biomimetic materials. In this review, we survey the current knowledge about teeth from representative mammals and aquatic animals, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 119 publications
(166 reference statements)
0
2
0
Order By: Relevance
“…While it has been observed that bats can predict aspects of the scene by accumulating sensor data [60], to the best of our knowledge, no concrete model on how this prediction might operate has been proposed in previous works. Other technical systems have been proposed to produce 3D scene reconstruction and semantic interpretation, [61], [62], but these proposed techniques utilize a teaching modality like LIDARs or cameras to perform a form of modality translation. Our SonoNERF model relies solely on acoustic data without the need for an additional supervision modality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has been observed that bats can predict aspects of the scene by accumulating sensor data [60], to the best of our knowledge, no concrete model on how this prediction might operate has been proposed in previous works. Other technical systems have been proposed to produce 3D scene reconstruction and semantic interpretation, [61], [62], but these proposed techniques utilize a teaching modality like LIDARs or cameras to perform a form of modality translation. Our SonoNERF model relies solely on acoustic data without the need for an additional supervision modality.…”
Section: Discussionmentioning
confidence: 99%
“…Our SonoNERF model relies solely on acoustic data without the need for an additional supervision modality. Furthermore, reference [62] does not use an acoustic sensing modality, causing the title to be somewhat misleading. Our approach follows the approach called ‘self-supervised learning’ which has received much attention in the recent years [63], [64].…”
Section: Discussionmentioning
confidence: 99%